Devonian–Carboniferous extension and Eurekan inversion along an inherited WNW–ESE-striking fault system in Billefjorden, Svalbard - Koehl, Jean-Baptiste P.; Allaart, Lis; Noormets, Riko (Zenodo, 2023)
Background: The Billefjorden area in central Spitsbergen hosts thick Lower–lowermost Upper Devonian, late–post-Caledonian collapse deposits presumably deformed during the Late Devonian Svalbardian Orogeny. These rocks are juxtaposed against Proterozoic basement rocks along the Billefjorden Fault Zone and are overlain by uppermost Devonian–early Permian deposits of the Billefjorden Trough, a N–S-trending Carboniferous rift basin bounded by the Billefjorden Fault Zone. Methods: We interpreted seismic reflection (also depth-converted), bathymetric, and exploration well data. Results: The data show abundant Early Devonian, WNW–ESE-striking (oblique-slip) normal faults segmenting the Billefjorden Trough, and a gradual decrease in tectonic activity from the Early Devonian (collapse phase) to early Permian (post-rift phase). Early Devonian–Middle Pennsylvanian WNW–ESE-striking faults were mildly reactivated and overprinted and accommodated strain partitioning and decoupling in the early Cenozoic. This resulted in intense deformation of Lower Devonian sedimentary rocks and in the formation of bedding-parallel décollements, e.g., between the Lower Devonian Wood Bay and the uppermost Pennsylvanian–lowermost Permian Wordiekammen formations. This suggests that intense deformation within Devonian rocks in Dickson Land can be explained by Eurekan deformation alone. Eurekan deformation also resulted in the formation of WNW–ESE- and N–S- to NNE–SSW-trending, kilometer-wide, open folds such as the Petuniabukta Syncline, and in inversion and/or overprinting of Early Devonian to Early Pennsylvanian normal faults by sinistral-reverse Eurekan thrusts. WNW–ESE-striking faults merge at depth with similarly trending and dipping ductile shear zone fabrics in Proterozoic basement rocks, which likely formed during the Timanian Orogeny. Conclusions: A NNE-dipping shear zone, which is part of a large system of Timanian thrusts in the Barents Sea, controlled the formation of WNW–ESE-striking Devonian–Mississippian normal faults and ...